Recent advances in aptamer-based biosensing technology for isolation and detection of extracellular vesicles - Osama Alnaser-Almusa; Mohammed Mahmoud; Mohammed Ilyas; Raghda Adwan; Farah Abul Rub; Noha Alnaser-Almusa; Fayrouz Mustafa; Sana Ahmed; Alaa Alzhrani; Alaa Alzhrani; Alaa Alzhrani; Tanveer Ahmad Mir; et al. (Frontiers in Cell and Developmental Biology)
Since their discovery in the 1970s, extracellular vesicles (EVs) have garnered significant scientific attention due to their involvement in diverse pathological processes, including tumorigenesis. Their unique properties have also piqued interest for various applications such as transporting biomolecules for drug delivery. Researchers have developed numerous isolation and detection methods for EVs, including ultracentrifugation, immunoaffinity capture, and antibody-based biosensors. However, these techniques often suffer from limitations in sensitivity, specificity, and efficiency, hindering their performance and reliability in research and clinical settings. Aptamers are short, single-stranded DNA or RNA molecules created to selectively bind to a specific target and offer a promising alternative to antibodies. These aptamers are identified by a process known as SELEX. By repeatedly selecting and amplifying aptamers with high binding affinity, SELEX can generate aptamers with exceptional specificity and sensitivity. Aptamers can then be incorporated into biosensors, known as aptasensors, for EV isolation, detection, and analysis. Aptasensors offer several advantages over antibody-based methods. They are often more stable, can be produced synthetically at lower cost, and can be easily modified for various applications. Additionally, aptamers can be selected against a wide range of targets, including proteins, nucleic acids, and small molecules, making them versatile tools for EV research. This review discusses various SELEX methods for aptamer detection, the clinical uses of aptamers, and the types of EV analysis methods.